Effect of traditional Chinese fitness exercises on bone mineral density in postmenopausal women: a network meta-analysis of randomized controlled trials - Liu, Shijie; Wu, Sijun; Qi, Juancai; Wang, Lin (Frontiers in Endocrinology, 2024)
We aimed to evaluate the clinical efficacy of five traditional Chinese fitness exercises (Baduanjin, Taijiquan, Wuqinxi, Yijinjing, and Liuzijue), as well as their efficacy when combined with drug therapy, in the treatment of decreased bone mineral density in postmenopausal women. Methods: This study strictly followed the evaluation guidelines of PRISMA and followed the “PICOS” principle outlined in the Cochrane Handbook. We performed a systematic search on Web of Science, Springer Link, Scopus, EMBASE, EBSCO, PubMed, the Cochrane Library, CNKI, Wanfang, CBMdisc, and the VIP Database, and we targeted RCTs studying the effect of TCE on BMD in postmenopausal women published prior to September 2023. The quality of the literature and the risk of bias of the included studies were assessed according to ROB2 and GRADE criteria, and data analysis was performed using Stata 14. Results: A total of 33 RCTs (3658 post-menopausal women) were included. Network meta-analysis showed that Taiji (SMD=0.72, 95% CI: 0.22, 1.21, P<0.01) and Yijinjing (SMD=0.51, 95% CI: 0.03, 0.99, P<0.05) were significantly superior to conventional rehabilitation in lumbar BMD. In terms of improvement of femoral neck BMD, Baduanjin (SMD=1.63, 95% CI: -3.58, 6.85, P<0.001) and Taiji (SMD=0.46, 95% CI: 0.14, 0.79, P<0.05) had statistically different outcomes to conventional rehabilitation. Regarding Ward's triangle BMD, Taiji (SMD= 0.32, 95% CI: 0.14, 0.50, P < 0.05) had statistically different outcomes to conventional rehabilitation. The results of the SUCRA probability ranking showed that Baduanjin + drug interventions achieved the most significant improvement in lumbar BMD (SUCRA=83.6%) and femoral neck BMD (SUCRA=90.2%). Taiji + drug interventions most effectively improved Ward’s triangle BMD (SUCRA=86.0%). In terms of traditional Chinese fitness exercises alone, Taiji was the most effective in improving lumbar BMD (SUCRA=64.4%) and Ward’s triangle BMD (SUCRA=46.8%), and Baduanjin was the most effective in treating femoral neck BMD (SUCRA=89.9%). Conclusions: Traditional Chinese fitness exercises can significantly improve the BMD levels of postmenopausal women. Taiji, Yijinjing, and Baduanjin combined with medication showed better intervention effects overall. However, due to the limitations of the number of studies and sample sizes of individual interventions, definitive conclusions need to be verified by more high-quality studies.